Combined full‐dose IV and endovascular thrombolysis in acute ischaemic stroke. Issue 8 (27th September 2012) - Bhatia, Rohit; Shobha, Nandavar; Menon, Bijoy K.; Bal, Simerpreet P.; Kochar, Puneet; Palumbo, Vanessa; Wong, John H.; Morrish, William F.; Hudon, Mark E.; Hu, William; Coutts, Shelagh B.; Barber, Phillip A.; et al.
Abstract : Background: There is an increasing trend to treating proximal vessel occlusions with intravenous–inter‐arterial (IV‐IA) thrombolysis. The best dose of IV tissue plasminogen activator (tPA) remains undetermined. We compared the combination of full‐dose IV recombinant tissue plasminogen activator (rtPA) and IA thrombolytic therapy to IA therapy. Methods: Between 2002 and 2009, we reviewed our computed tomographic angiography database for patients who received full‐dose intravenous rtPA and endovascular therapy or endovascular therapy alone for acute ischaemic stroke treatment. Details of demographics, risk factors, endovascular procedure, and symptomatic intracranial haemorrhage were noted. Modified Rankin Scale ≤2 at three‐months was used as good outcome. Recanalization was defined as Thrombolysis in Myocardial Ischaemia 2–3 flow on angiography. Results: Among 157 patients, 104 patients received IV‐IA treatment and 53 patients underwent direct IA therapy. There was a higher recanalization rate with IV‐IA therapy compared with IA alone (71% vs. 60%, P < 0·21) which was driven by early recanalization after IV rtPA. Mortality and independent outcome were comparable between the two groups. Symptomatic intracranial haemorrhage occurred in 8% of patients (12% in the IA group, 7% in the IV‐IA group) but was more frequent as the intensity of intervention increased from device alone to thrombolytic drug alone to device plus thrombolytic drug(s). Recanalization was a strong predictor of reduced mortality risk ratio (RR) 0·48 confidence interval95 0·27–0·84) and favourable outcome (RR 2·14 confidence interval95 1·3–3·5). Conclusions: Combined IV‐IA therapy with full‐dose intravenous rtPA was safe and results in good recanalization rates without excess symptomatic intracranial haemorrhage. Testing of full‐dose IV tPA followed by endovascular treatment in the IMS3 trial is justified.